Essentials of Cataloging and Classifications by Dr. KM Saiful Islam (Journal of the Bangladesh Association of Young Researchers, 2011)
DOI: 10.3329/jbayr.v1i1.6951Journal of Bangladesh Association of Young Researchers Vol.1(1) 2011 pp.133-134